Weeders for Drudgery Reduction of Women Farm Workers in India - Singh, Suman; Mathur, Puja; Rathore, Madhu (Journal of Agricultural Engineering, 2007)
Women play a vital role in agriculture. Rural women perform the entire household activities as well as they are employed in most arduous field operations. They are also engaged in post harvest and agro-processing activities. Weeding activity is predominantly carried out by women. Weeding activity is a strenuous one and the odd posture adopted by women while weeding may increase the heart rate out of proportion and lead to irreparable damage to the body. The present research assesses three types of weeders on ergonomic parameters with a view to promote health, efficiency and consequently improving the quality of work life. The study was conducted in vegetable fields on 30 farm women in the age group of 25-40 years having normal blood pressure, body temperature and not suffering from any chronic illness. Ergonomic cost of weeding activity was calculated in terms of heart rate and energy expenditure. Body map technique was used to assess the musculo-skeletal discomfort of the workers. Results of the study revealed that all three weeders proved efficient on ergonomic parameters; reduced average working heart rate, energy expenditure and output as compared to traditional tool. The posture improved while working with weeders as the bending and squatting posture employed while weeding with traditional method was replaced by standing posture.